Síntese e caracterização de nanopartículas de ferro produzidas com extrato de chá verde - Sousa, Amanda Lima (2023)
This study aims to develop iron nanoparticle solutions in an economically accessible way, using extract from the leaves of national green tea (Camellia sinensis) sold in bulk. The research uses advanced green nanobiotechnology techniques to improve synthesis methodologies in aqueous media, ighlighting the use of low-cost reagents and materials, such as green tea leaves. The stability of nanoparticle colloidal solutions was investigated using Infrared Spectroscopy (FTIR) and Atomic Force Microscopy (AFM). The detailed characterization of the nanoparticles includes the analysis of size, shape and availability of chemical groups, in addition, the nanoparticles were purified using the centrifugation method. The results revealed the successful obtaining of nanoparticles with an average diameter of 56 nm, demonstrating the effectiveness of the proposed method. FTIR analyzes demonstrate the presence of green tea polyphenols in the nanoparticles, indicating an effective association between the tea extract compounds and the iron nanoparticles. This study contributes to the advancement of iron nanoparticle synthesis techniques in an accessible way, using natural sources such as green tea, with promising implications for applications in various fields, such as medicine and industry.